Flood inundation assessment under climate change scenarios in Kuantan River Basin, Malaysia - Winarta, Bambang; Juwono, P. T.; Dermawan, V.; Mohamad Idris, Ali; Noram Irwan, Ramli (IOP Publishing Ltd., 2019)
The changing of climate pattern will increase the magnitude and frequency of excessive precipitation events which may trigger the possibility of river flooding with more severe and with higher risks. The objective of this current study is to assess and determine the flood inundation at the midstream to downstream part of Kuantan River Basin without and with consideration on Climate Change Factor (CCF). This coefficient is obtained from a technical guide on future design rainstorm with Climate Change Factor (CCF) by National Hydraulic Research Institute of Malaysia (NAHRIM). Next, design storm used in this study is a 24-hour storm duration and 100 years Annual Recurrence Interval (ARI). The finding of this study shows that climate change brings a significant impact on flood inundation depth and also in area. This result will be useful for city and or state government in term of formulating of appropriate strategies in order to minimize the negative impacts of flooding in Kuantan River Basin.